Protection And Legal Responsibility For BPJS Patient Medical Records In The Perspective Of Legal Certainty - Setya, Clarita Ayu Putri; Kholib, Abdul; Prasetyo, Handoyo (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
Medical records as a record are the responsibility and obligation of every medical and health worker to keep the health data of the patients they handle confidential. However, in 2021 there was a data leak from BPJS Health membership patients, where there were 279 million records of BPJS Health patient personal data information spread and traded on Raid Forums. Then it happened again in early 2022. This research aims to analyze and describe the protection and legal responsibility for the medical records of patients of the Social Security Organizing Agency in the perspective of legal certainty and to analyze and describe the implementation of the regulation of patient medical records of the Social Security Organizing Agency based on applicable provisions. This research uses empirical normative legal methods (Socio-Legal). The results of the study show that the implementation of the regulation of medical records of patients of the Social Security organizing agency is technically carried out on the basis of the Minister of Health Regulation Number 24 of 2022 concerning Medical Records. In the regulation, there are conditions that are difficult to distinguish related to the responsibility of the Ministry of Health and the relevant hospitals. The researcher concludes that the policy of protection and legal responsibility for the medical records of patients of the Social Security organizing body in the perspective of legal certainty is currently not fully realized.